The Value of Magnetic Resonances Imaging in Localized Lipoatrophy - (:unkn) unknown (BEZMIALEM VAKIF UNIV, 2019)
Localized lipoatrophy usually presents as isolated or multiple, atrophic, depressed areas which are commonly found in the proximal part of extremities. We report a case with idiopathic localized lipoatrophy and want to emphasize the role of magnetic resonance imaging in the evaluation of atrophic lesions.
Keywords: Lipoatrophy; idiopatic localized; magnetic resonance imaging; INVOLUTIONAL LIPOATROPHY